2003
DOI: 10.2139/ssrn.472762
|View full text |Cite
|
Sign up to set email alerts
|

Employment Protection Legislation and the Size of Firms

Abstract: Employment Protection Legislation and the Size of Firms * The existing literature ignores the fact that in most European countries the strictness of Employment Protection Legislation (EPL) varies across the firm size distribution. In Italy firms are obliged to rehire an unfairly dismissed worker only if they employ more than 15 employees. Theoretically, the paper solves a baseline model of EPL with threshold effects, and shows that firms close to the threshold are characterized by an increase in inaction and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 7 publications
6
44
0
2
Order By: Relevance
“…Employment protection legislation, which imposes higher unfair dismissal costs on firms that employ more than 15 employees, was found to reduce business size and growth for firms that were just below the size threshold. Using the same data source, Garibaldi et al (2004) find results that are consistent with Schivardi et al (2004). The German Protection Against Dismissal Act allows firms above a certain size threshold to sue for wrongful termination.…”
Section: Literature Reviewsupporting
confidence: 87%
“…Employment protection legislation, which imposes higher unfair dismissal costs on firms that employ more than 15 employees, was found to reduce business size and growth for firms that were just below the size threshold. Using the same data source, Garibaldi et al (2004) find results that are consistent with Schivardi et al (2004). The German Protection Against Dismissal Act allows firms above a certain size threshold to sue for wrongful termination.…”
Section: Literature Reviewsupporting
confidence: 87%
“…Kugler andPica (2003, 2008) have analyzed the e¤ect of this reform, and found that both in ‡ow and out ‡ow of employment in small …rms decreased after the reform relative to the corresponding ‡ows in larger …rms. Similar results were obtained by Cingano et al (2010), Garibaldi et al (2004), who showed that job reallocation decreased in small …rms after the reform in Italy. Schivardi and Torrini (2004) studied the e¤ects of the same reform on the …rm size distribution in Italy.…”
Section: Empirical Studiessupporting
confidence: 86%
“…Their results indicated that removing the threshold in Italian EPL would increase average …rm size by less than 1 percent. These results are supported by Garibaldi et al (2004), who found that …rms close to the 15 employees shows more persistence than other …rms, and that they are more likely to move backward than upward.…”
Section: Empirical Studiessupporting
confidence: 61%
“…Ichino et al (2003) argue that judges are biased by labour market conditions in their court ruling. Garibaldi et al (2004) study the effect of a size threshold in the reinstatement clause, and find that there is some evidence of an increase in employment persistence around the threshold, but the size of the effect is quantitatively small. This paper studies a deferred wage scheme, called Trattamento di Fine Rapporto (Remuneration upon Separation, TFR in the rest of the paper).…”
Section: Deferred Wages In the Italian Institutional Settingmentioning
confidence: 99%